2014
DOI: 10.5433/1679-0359.2014v35n4p1697
|View full text |Cite
|
Sign up to set email alerts
|

Épocas de aplicação e concentrações de ácido abscísico no incremento da cor da uva ‘Isabel’

Abstract: ResumoA uva 'Isabel', principal cultivar utilizada para a elaboração de suco no Brasil, apresenta deficiência de cor, sendo uma das alternativas, a aplicação do ácido abscísico (S-ABA), visto que o acúmulo de antocianinas, pigmento que interfere na cor das bagas, parece ser regulado, por este fitohormônio. O objetivo do trabalho foi avaliar o efeito de concentrações de S-ABA, aplicadas em épocas distintas nos cachos da videira 'Isabel', na melhoria dos atributos de cor. As videiras foram conduzidas em espaldei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 8 publications
4
17
0
4
Order By: Relevance
“…It can be inferred that the application of this growth regulator does not affect the physical characteristics related to the productivity of 'Isabel' grape. Similar results were reported by Koyama et al (2014aKoyama et al ( , 2014b, who studied the effects of different concentrations and frequencies of S-ABA application at veraison on the same cultivar.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…It can be inferred that the application of this growth regulator does not affect the physical characteristics related to the productivity of 'Isabel' grape. Similar results were reported by Koyama et al (2014aKoyama et al ( , 2014b, who studied the effects of different concentrations and frequencies of S-ABA application at veraison on the same cultivar.…”
Section: Resultssupporting
confidence: 73%
“…When studying S-ABA application at veraison to 'Isabel' grape, Koyama et al (2014a) observed a different relationship for the increment in anthocyanin concentration in berries in the juice, with the application of 200 and 400 mg L -1 S-ABA, independently of the application frequency. In contrast, for whole juice, the concentration of 400 mg L -1 applied once or twice was more effective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant regulators have been used in several grape growing regions around the world in order to overcome color problems. Recently, it has been demonstrated that the exogenous application of (S)-cis-abscisic acid (S-ABA) can overcome the lack of color in colored grapes through the synthesis of anthocyanins, which are pigments that impart color to the fruits (Roberto et al, 2012;Koyama et al, 2014).…”
Section: Introductionmentioning
confidence: 99%